Kampanye Energi Terbarukan dan Nilai Inklusi Untuk Meningkatkan Pengetahuan Siswa Pada SMAN 3 Timang Gajah - Zulnazri; Ahmad Fikri Fikri; Agam Muarif; Sri Rahayu Retnowulan (Kreativasi : Journal of Community Empowerment, 2023)
Electrical energy is an important today. Electrical energy still comes from fossils. It is can produce carbon gas emissions and cause greenhouse gas effects. Clean energy conversion is something that must be done immediately. This clean energy conversion still has obstacles in the form of negative public views regarding new renewable energy. Negative perspective is the effectiveness of using EBT and the need for large enough land, thereby reducing agricultural land in the future. Young people are the most strategic objects in society for implementing EBT changes in the future. The problem is the lack of knowledge among young people regarding the potential use of EBT and the limited number of competent facilitators to provide material regarding EBT. Therefore, it is necessary to carry out EBT activities and inclusive values among young people to increase competence in understanding EBT. This activity is carried out with a campaign and simulation with a solar power plant works. The aim of this activity is that students are able to choose and apply EBT in community life. The activity indicator is that students can provide feedback and explain how solar power plants work.